Human-Wildlife Conflict and Its Implication for Conservation around Bwindi Impenetrable National Park - Aharikundira, Margaret; Tweheyo, Mnason (Rocky Mountain Research Station, 2011)
This study analyzed the impact of wildlife on farmers who lived around the Bwindi Impenetrable National Park (BINP). The objectives were to assess the extent of damage exerted upon local farmers and to establish problem animal control strategies employed for park management and community members. Respondents identified crop loss as the major form of damage (40%), followed by social disruption (35%), damage to property (30%) and threats to human life (20%). The majority of the farmers (63%) reported that the park did not employ any measures to protect people's crops. Very small percentages recognized that the park management employed fencing, vermin guards, and HUGO, as preventive measures to guard against raiding of the peoples’ crops. The study concludes that maize, sweet potatoes, and sorghum were the most frequently raided crops. This report recommends integrated management for conservation activities around the park, and integration of local communities into planning, management, and decision making of the Bwindi Impenetrable National Park.
Keywords: Conflict; Conservation; Wildlife